Implementasi Model Pembelajaran Kooperatif Tipe Numbered Heads Together (NHT) Dalam Meningkatkan Pemahaman Siswa Pada Mata Pelajaran Fikih - Zaifatur Ridha; Nurmisdaramayani Nurmisdaramayani; Ajeng Alfinda (Fakultas Syariah IAIN Laa Roiba Bogor, 2020)
The results of observations and interviews at MTs Jam'iyah Mahmudiyah Tanjung Pura on students and teachers showed that students' understanding of the subject of Fiqh was low. This is because teachers still use a monotonous or conventional learning model. The purpose of this study was to determine the application of the Numbered Heads Together (NHT) cooperative learning model in understanding the subjects of Jurisprudence. The research method used is Classroom Action Research (CAR). The object of this research is class VIII D students, totaling 29 students. Data collection is done by observation, interviews, tests and documentation. Data analysis uses quantitative calculations which are then described in the form of percentages. Based on the results of the pre-test and post-test, students' understanding after using the Numbered Heads Together (NHT) cooperative learning model increased each cycle. In the implementation of the pre-test, the level of student understanding was obtained with a percentage figure of 51.72%. In the first cycle, the percentage figure was 75.86% and there was an increase in the implementation of the second cycle by obtaining a percentage figure of 93.10%.